The Significance of FDI Inflow and Renewable Energy Consumption in Mitigating Environmental Degradation in Somalia - Warsame, Zakarie Abdi (International Journal of Energy Economics and Policy, 2023)
This study explores the impact of foreign direct investment (FDI), renewable energy, gross capital formation, population growth, gross domestic product (GDP), and the square of GDP on carbon dioxide (CO2) emissions in Somalia between 1990 and 2019. To investigate the short- and long-run elasticity of environmental degradation and the other variables, the autoregressive distributed lag (ARDL) model is employed. In Somalia, the long-run coefficients of the ARDL model indicate that renewable energy contributes negatively to environmental degradation. At the same time, domestic investment and population growth undermine the quality of the environment. Furthermore, the FMOLS results validate the existence of EKC in Somalia. The Granger causality test is also applied to investigate the causal relationship between the variables. Despite this, there was no evidence that FDI and renewable energy are causally related to environmental degradation. Based on our empirical assessment, the Somali government should encourage foreign direct investment, especially in technology-intensive and environmentally friendly industries, and pay increased attention to the improvement and consumption of renewable energy sources.